Inside Cisco IOS software architecture - Bollapragada, Vijay; Murphy, Curtis; White, Russ.; Safari eBooks (Indianapolis, IN : Cisco Press, 2000)
"Inside Cisco IOS Software Architecture begins with an overview of operating system concepts and the IOS Software infrastructure, including processes, memory management, CPU scheduling, packet buffers, and device drivers, as well as a discussion of packet switching architecture with detailed coverage of the various platform-independent switching methods, including process switching, fast switching, optimum switching, and Cisco Express Forwarding (CEF). The book then delves into the intricate details of the design and operation of platform-specific features, including the 1600, 2500, 4x00, 3600, 7200, 7500, and GSR Cisco routers. Finally, an overview of IOS Quality of Service (QoS) is provided, including descriptions of several QoS methods, such as priority queuing, custom queuing, weighted fair queuing, and modified deficit round robin"--Resource description page.
Fundamental IOS software architecture -- Packet switching architecture -- Shared memory routers -- Early Cbus routers -- Particle-based systems -- Cisco 7500 routers -- The Cisco gigabit switch router : 12000 -- Quality of service -- Appendix: NetFlow switching.
Description based on print version record.
Includes index.
Keywords: Cisco IOS; Computer network architectures; Systems software; Software architecture; Electronic books